1998
DOI: 10.1016/s0370-2693(98)00246-9
|View full text |Cite
|
Sign up to set email alerts
|

Feynman diagrams as a weight system: four-loop test of a four-term relation

Abstract: At four loops there first occurs a test of the four-term relation derived by the second author in the course of investigating whether counterterms from subdivergencefree diagrams form a weight system. This test relates counterterms in a four-dimensional field theory with Yukawa and φ 4 interactions, where no such relation was previously suspected. Using integration by parts, we reduce each counterterm to massless two-loop two-point integrals. The four-term relation is verified, with G 1 − G 2 + G 3 − G 4 = 0 −… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Also, in a parallel paper, we will present an explicit 4-loop calculation which establishes the 4TR as proposed here, and demonstrates its failure in cases when our derivation is not applicable [15].…”
Section: The Four-term Relationmentioning
confidence: 89%
See 1 more Smart Citation
“…Also, in a parallel paper, we will present an explicit 4-loop calculation which establishes the 4TR as proposed here, and demonstrates its failure in cases when our derivation is not applicable [15].…”
Section: The Four-term Relationmentioning
confidence: 89%
“…An example is when I 3,2 provides a subdivergence at s 2 = 0, while I 8,2 does only so at s 2 = 0. This asymmetry provides us finally with an extra contribution which diverges with λ, which can be shown to have the form of a finite part of a two-loop integral of master topology [15]. A more detailed analysis will be given elsewhere.…”
Section: Propositionmentioning
confidence: 97%
“…In this paper, we investigated the 4-term relation for chord diagrams, which was shown to hold in some cases in [6], but found no such relation on the level of c 2 invariants in φ 4 theory. To our surprise, however, we found that the 4-term identity actually holds true on the level of the denominator polynomials D 7 G .…”
Section: Combinatorial Identitiesmentioning
confidence: 99%
“…If we subtract 2h [1], and the theorem follows. (6) and N G/ /e = 0 or N G/ /e ≥ h G/ /e + 1, hence q|[Ψ G/ /e ] q . Again, the theorem follows.…”
Section: Proposition 15mentioning
confidence: 99%
“…We shall show that the dispersive methods of [4,5] enable a reduction of C T et , as for any assignment of masses, to single integrals of logarithms. Then we shall describe how the lattice algorithm PSLQ [6] achieved a very simple reduction of C T et to a Clausen integral, which gives an exponentially convergent sum that reveals a new feature of the distinctive mapping [7] of diagrams [5,8,9,10,11,12] to numbers [13,14,15,16] provided by quantum field theory.…”
Section: Introductionmentioning
confidence: 99%